Optimizing EDM Process Parameters for Enhanced Surface Finish and Metal Removal Rate (MRR) - Nishant Mani; Dr. Rahul Mishra (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
Electrical Discharge Machining (EDM) has emerged as a vital non-traditional machining process for producing complex geometries and machining hard-to-cut materials with high precision. Unlike conventional methods, EDM relies on thermoelectric energy in the form of controlled electrical discharges between the tool and workpiece immersed in a dielectric medium. Among the critical challenges in EDM, achieving a balance between material removal rate (MRR) and surface finish has been widely acknowledged. Higher discharge energy generally enhances MRR but deteriorates surface quality, while lower energy settings improve smoothness at the cost of reduced productivity. This study investigates the underlying mechanisms governing this trade-off and explores process parameter optimization for simultaneous improvement in MRR and surface finish. Experimental trials were conducted using varying pulse currents, discharge voltages, and duty cycles to evaluate their effects on machining performance. Surface roughness (Ra) was measured using a profilometer, while MRR was calculated based on weight loss method. The results reveal that moderate discharge energy combined with optimized duty cycle significantly improves MRR without compromising surface smoothness. The thermal and physical mechanisms, including controlled crater formation and plasma channel stabilization, are identified as key contributors to this improvement. The experimental findings demonstrate that optimized pulse current and duty cycle lead to an improvement of up to 20–25% in MRR while simultaneously reducing surface roughness by nearly 15% compared to conventional settings.
Keywords: Electrical Discharge Machining; Material Removal Rate; Surface Roughness; Process Optimization; Discharge Energy; Thermal Mechanism